Strategi Ekonomi Dalam Upaya Membangkitkan Kembali Perdagangan Rotan Di Kota Makassar - Lastri Liana (Jurnal Ekonomi dan Riset Pembangunan, 2023)
This study aims to determine: the process of rattan trade revival in the city of Makassar, the dynamics of the rattan trade, and the resulting socio-economic impacts. This type of research is descriptive in nature with a qualitative approach. The data collection process is carried out through observation, interviews, and documentation. The results of the study show that the city of Makassar has long been known as a trade gateway and regional economic center in eastern Indonesia. Several areas supplying rattan commodities in Makassar, namely: Mamuju, Palopo, Enrekang, Palu, Kendari, and also from Kalimantan. Rattan raw materials are obtained by craftsmen in Makassar City through transportation from various regions both by land and by sea through the port of Makassar. The types of rattan used as furniture are rattan symbols, stems, tohiti, datu, and umbulus. Craftsmen in Makassar produce semi-finished rattan, which is then sent to Surabaya and thereafter exported. The revival of the rattan trade has had a positive impact on society and the government, namely opening up employment opportunities and increasing the country's foreign exchange.